Modelling Transport of Heavy Metals in Geita Wetland along Mamubi River - Masawe., Ezrael, J.; Kimwaga., Richard; Mwanuzi., Fredrick (Tanzania Journal of Engineering and Technology, 2018)
The modelling of heavy metals in rivers is highly dependent on hydrodynamics, the transport of suspended particulate matter and the partition between dissolved and particulate phases. This paper presents the development of hydrodynamic model DUFLOW, which is a one dimensional flow and water quality simulation package, that describes the processes governing transformations and transport of heavy metals (Hg, Ni and Cu) along Mabubi River in the Geita wetland. Two monitoring stations were established along Mabubi River at the inlet (MBSP1) and outlet (MBSP2) of the wetland. A set of DUFLOW model inputs representative of the water conditions were collected from the established monitoring stations. The model was calibrated and validated for the prediction of flow and heavy metals (Hg, Ni, and Cu) transport, against a set of measured mean monthly monitoring data. Sensitive model parameters were adjusted within their feasible ranges during calibration to minimize model prediction errors. At the gauging station MBSP2, the calibration results showed the model predicted mean monthly flow within 17% of the measured mean monthly flow while the r2 coefficient and Nash-Sutcliffe (NSE) were 0.83 and 0.79 respectively. At the water quality monitoring station MBSP2, the calibration results showed the model predicted heavy metals (Hg, Ni and Cu) concentrations within 13% and 17% of their respective measured mean monthly concentrations. The mean monthly comparisons r 2 values for heavy metals ranged from 0.75 to 0.88 while the NSE values were between 0.70 and 0.82. The model results and field measurements demonstrated that about 40% of the annual heavy metals loadings which would otherwise reach the Lake Victoria are retained in the wetland. The Mabubi river model can therefore be used for prediction of heavy metals (Hg. Ni and Cu) transformation processes in the Geita wetland. Keywords: Copper, DUFLOW, Geita wetland, Mabubi River, Mercury, Nickel